Relationship between personality traits and coping styles among Malaysian young adults - Chin, Kong Lek; Labent, Shirly Anak; Xin Lin, Jasmine Wong; Chan, Siaw Leng (Human Resources Management Academic Research Society (HRMARS), 2024)
Given the increasing prevalence of stress and anxiety, which permeates all aspects of society and affects people of all ages and backgrounds, understanding how coping styles and personality traits are related is crucial to coping with everyday challenges and stressors. This study examined the relationship between personality traits and coping styles among Malaysian young adults. This study utilized a cross-sectional survey method. A total of 252 young adults participated in this study using purposive sampling, and the data were collected through a survey using a set of questionnaires, namely, the Big Five Inventory (BFI) and the Brief-COPE. The finding showed that personality traits and coping styles are positively correlated. Alongside this, there were intriguing gender differences in the use of avoidance coping among Malaysian young adults. However, this study found no differences in the coping styles used by different genders in emotion-focused and problem-focused coping. This study concluded that problem-focused coping was utilized the most by Malaysian young adults compared with emotion-focused and avoidant coping. The findings of this study highlighted that young Malaysian adults, with their proactive coping approach, are hopeful and optimistic about addressing challenges and stress. Implications and future recommendations are discussed.